Associations of self-reported physical activity levels and lifestyle risk factors with irritable bowel syndrome severity scores - Yu, Chang Zhuang (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Objectives: The purpose of this study was to explore the relationship between various components of self-reported physical activity levels, lifestyle factors and irritable bowel severity scores in irritable bowel syndrome (IBS) patients. Methods: thirtyeight IBS patients who previously sought treatment from Hospital Universiti Sains Malaysia were recruited in this study. They were asked to complete the International Physical Activity Questionnaire (IPAQ), IBS Severity Scoring System (IBS-SSS) and, lifestyle and dietary questionnaires and fill the personal demographic data form. We used multiple regression analysis to investigate the influence of physical activity and lifestyle factors on IBS severity scores. Result: There is no significant difference in the self-reported physical activity levels among IBS patients (p>0.05). We were unable to find any significant relationship between self-reported physical activity levels on the IBS severity scores of IBS patients (p>0.05). There is also no significant relationship between lifestyle factors on the IBS severity scores of IBS patients (p>0.05) except the frequency of fermented food intake showed a significant relationship on the IBS severity score (β = 0.313, p=0.040). Conclusion: The frequency of fermented food intake is a predictor of IBS severity level. Physical activity levels, longer sitting time, intra-meal fluid intake, chewing insufficiency, higher tooth loss and the consumption of spicy and fried food were not associated with increased severity of IBS.